2011
DOI: 10.1007/s13142-011-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

A computerized, tailored intervention to address behaviors associated with PTSD in veterans: rationale and design of STR2IVE

Abstract: Combat exposure among military personnel results in increased risk of posttraumatic stress disorder (PTSD), major depression, substance use, and related health risks. PTSD symptoms require innovative approaches to promote effective coping postdeployment. PTSD's nature and scope requires an approach capable of integrating multiple health risks while reaching large populations. This article provides the rationale and approach to adapt and evaluate a Pro-Change computerized tailored intervention (CTI) targeted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The measure has demonstrated good internal consistency in different populations with chronic illness (α = .82 to .92; Burckhardt et al, 1989) as well as high test–retest reliability and evidence for convergent and discriminant validity (Burckhardt & Anderson, 2003). The QOLS has been utilized in a number of studies to assess for perception of quality of life with military veterans diagnosed with PTSD (e.g., Jordan, Evers, Burke, King, & Nigg, 2011; Resnik, Gray, & Borgia, 2011). Burckhardt and Anderson (2003) report that there is some evidence that the QOLS is sensitive to symptom change.…”
Section: Methodsmentioning
confidence: 99%
“…The measure has demonstrated good internal consistency in different populations with chronic illness (α = .82 to .92; Burckhardt et al, 1989) as well as high test–retest reliability and evidence for convergent and discriminant validity (Burckhardt & Anderson, 2003). The QOLS has been utilized in a number of studies to assess for perception of quality of life with military veterans diagnosed with PTSD (e.g., Jordan, Evers, Burke, King, & Nigg, 2011; Resnik, Gray, & Borgia, 2011). Burckhardt and Anderson (2003) report that there is some evidence that the QOLS is sensitive to symptom change.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies emphasize the relevance and benefits of audience segmentation and tailoring messages to specified populations [ 64 ]. For instance, tailored internet-based messages were found to be beneficial for intervening with patients with mental health issues such as trauma, because they offer anonymity, reduce fear of stigma, and increase self-disclosure [ 65 ]. Rayens et al have indicated the need to tailor smoke-free media campaigns in the U.S. to the rural populations that are more exposed to tobacco, focusing more on the benefits of smoke-free environments in gain-framed ads, as opposed to the different approaches recommended for use with urban residents [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these publications (n ¼ 5) described interventions that were designed for US military veterans (Table 3). [43][44][45][46][47] Two other interventions were designed for civilian populations who had experienced mass disaster. 48,49 Most interventions utilized webbased modules, although one included telehealth treatment with a handheld electronic device.…”
Section: Published Protocols and Feasibility Studiesmentioning
confidence: 99%
“…While one research group did combine a module-based approach with telehealth from a health care provider, 43,46 most of the feasibility and protocol publications did not include technology-facilitated human contact. 44,45,[47][48][49] Generally, these approaches also incorporate treatment for several types of substance use, including alcohol, drug use and smoking. This range of treatment options may allow for application to a wider patient population, since it allows for users to opt into relevant treatment modules based upon screening information.…”
Section: Technology-based Mode Of Treatment Deliverymentioning
confidence: 99%